Micro air vehicles : flapping wing propulsion - Koay, Say Seng. (2011)
This Final Year Report (FYP) investigated the aerodynamic effects of a flapping wing. A water tunnel facility was used in the experiments, testing the effects of a wing in heaving motion on a constant, steady flow. The wing used was a straight wing of airfoil NACA 0012. Two different methods were used separately in the experiments, namely using a pitot static tube and using constant wire anemometry.